SINTESIS METIL ESTER DARI MINYAK DEDAK PADI MENGGUNAKAN KATALIS KALIUM DENGAN PENGEMBAN ZEOLIT ALAM - Arif Hidayat; Septya Chilya Faizah; Resita Trisnaningtyas (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
Biodiesel is an alternative renewable energy source having many advantages such as environmental friendly, non-toxic, and has lower emission gases. Biodiesel is produced from transesterification of vegetable oils or animal fat. In this research, the transesterification of rice barn oil (RBO) using the solid base catalyst was studied. The performances of the catalysts were evaluated in terms of the reaction temperatures, the molar ratios of methanol to oil, and the catalyst loading. The effects of the mass ratio of catalyst to oil (1-10%), the molar ratio of methanol to oil (6:1-12:1), and the reaction temperature (40-60 oC) were studied for the yield of biodiesel to optimize the reaction conditions. The results showed that the optimal conditions were a methanol to oil molar ratio of 12:1, the amount of catalyst of 10%wt. of oil, and reaction temperature of 60 oC. The physicocharacteristics of the catalysts were analyzed by Nitrogen gas adsorption, surface functional groups by Fourier transform infrared spectroscopy (FT-IR), X-Ray Fluorescence Spectroscopy (XRF), and XRay Diffraction (XRD).